A Matric Flux Potential Approach to Assess Plant Water Availability in Two Climate Zones in Brazil - Pinheiro, E.A.R. (2020)
Predicting soil water availability to plants is important for agricultural and ecological models. Models that explicitly take into account root water uptake and transpiration reduction describe the ability of soil to supply water to plants based on soil hydraulic properties that depend on soil water content. The objective of this study was to further develop an existing single‐layer root water uptake model based on matric flux potential to allow for multi‐layer scenarios; and to illustrate its functionality using soil hydraulic properties from layered soils from two climate zones in Brazil: a semiarid zone and a humid zone. For each soil layer, the hydraulic properties were determined by inverse modeling of laboratory evaporation experiment data available for pressure heads between −165 and −1.5 m. The water supplying capacities of soils were evaluated using the newly developed multi‐layer root water uptake model. Soils from the semiarid zone were able to supply water to plants over a wider range of pressure heads. Soils from the humid zone showed slightly stronger hydraulic restrictions for supplying transpirable water. For the analyzed soils, only a negligible increase in available water results from decreasing the root water potential below −150 m. Therefore, based on this analysis, it is reasonable to expect plant adaptation to move toward an increase of root length density rather than to a decrease of minimum root water potential.